EFFICACY OF PROPOLIS AS FEED ADDITIVES ON GROWTH AND HEMATOLOGICAL PARAMETERS ON CYPRINUS CARPIO CHALLENGED WITH AEROMONAS HYDROPHILA - Maymounah. A. Al-Gburi,; S. A. Mustafa, (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2025)
The present study was conducted to investigate the effects of propolis [(crud propolis and Water Ethanol Extract Propolis (WEEP)] as feed additive on growth performance, hematology and survival rate in common carp, Cyprinus carpio challenged with Aeromonas hydrophila. A total of 60 C. carpio, (average weight 75±10g) were randomly distributed into five treated groups as follows: control group (C) fish were fed basal diet without any addition of propolis; T1 fish were fed basal diet supplemented with 10g/kg crud propolis; T2, T3 and T4 fish were fed WEEP at concentrations of 2g, 4g and 8 g/kg diet respectively for 42 days. Results indicated that the best Final weight, specific growth rate (SGR%) and feed conversion ratio (FCR) were observed in T2 followed by T1 compared to control and other treated groups. At the end of the feeding period, fish were intraperitoneally challenged by A. hydrophila. The survival rate recorded highest value (100%) in T2 compared to control positive group (42%).  Hematological indices showed considerable changes in the mean values of RBCs, Hb, PCV and WBCs. This study suggests that growth performance and survival rate against   any infection with A. hydrophila of common carp can be improved by dietary supplementation with crude propolis and WEEP propolis at concentration of 2 g/kg diet which is beneficial for fish culture.